2006
DOI: 10.2136/sssaj2005.0249
|View full text |Cite
|
Sign up to set email alerts
|

Management Effects on Soil Physical Properties in Long‐Term Tillage Studies in Kansas

Abstract: Five long-term tillage studies in Kansas were evaluated for changes in soil properties including soil organic carbon (SOC), water holding capacity (WHC), bulk density, and aggregate stability. The average length of time these studies have been conducted was 23 yr. Soil properties were characterized in three depth increments to 30 cm, yet changes due to tillage, N fertility, or crop rotation were found primarily in the upper 0-to 5-cm depth. Decreased tillage intensity, increased N fertilization, and crop rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
104
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 23 publications
17
104
2
5
Order By: Relevance
“…Under this situation residues retained on soil surface did not significantly reduce BD. Similar result for soil bulk density was reported by McVay et al (2006) who found that below 3 cm soil depth BD values were only minimally affected by management practices. At lower depths under conventional tillage, higher BD might be due to the formation of a traffic pan.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Under this situation residues retained on soil surface did not significantly reduce BD. Similar result for soil bulk density was reported by McVay et al (2006) who found that below 3 cm soil depth BD values were only minimally affected by management practices. At lower depths under conventional tillage, higher BD might be due to the formation of a traffic pan.…”
Section: Resultssupporting
confidence: 90%
“…At lower depths under conventional tillage, higher BD might be due to the formation of a traffic pan. Higher BD at surface soil of Sc3 and Sc4 than Sc2 might be due to machine induced compaction (McVay et al 2006). Soils higher in SOC are not prone to compaction, which may help explain why so little change in bulk density occurred at the CA-based scenarios (McVay et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the crop effect was not stable over time and no long-term crop rotation effects could be demonstrated. McVay et al (2006) reported effects of tillage and crop rotation from five trials in a continental climate in Kansas, USA, all having silt loam soils. Changes were found only in the upper soil layer from 0 to 5 cm.…”
Section: Organic Matter Inputmentioning
confidence: 99%
“…The impact of organic matter on aggregation is greater in soils containing less than 25% clay, while in soils containing more than 35% clay the correlation is less significant. Li and Shao (2006), Quiroga et al (1998) and McVay et al (2006) showed that increased porosity and decreased bulk density occurred as a result of increased content of soil organic matter and aggregate stability. Soil physical properties are also affected by parent rock and terrain incline (Breuer et al 2006).…”
mentioning
confidence: 99%